Silicon dioxide powder
By heating silicon dioxide in the presence of halogen, the silicon dioxide powder achieves a low uranium content and high sphericality, addressing the challenge of α-ray emission in semiconductor encapsulating materials and improving semiconductor device reliability.
Patent Information
- Application Number
- JP2023511032
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-22
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2042-03-22
AI Technical Summary
The increasing complexity of semiconductor circuits demands further reduction in α-ray emission from semiconductor encapsulating materials, which are currently limited by high uranium content in silicon dioxide powders used as fillers.
Heating silicon dioxide in the presence of halogen to produce a silicon dioxide powder with a uranium content of 0.8 mass ppb or less and a high sphericality, while also controlling specific surface area and particle size distribution.
The resulting silicon dioxide powder effectively reduces α-ray emission, enhancing the reliability of semiconductor devices by minimizing memory errors, and maintains high flowability and purity suitable for semiconductor encapsulants.
Smart Images

Figure 0007656692000002 
Figure 0007656692000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicon dioxide powder suitable for use in semiconductor encapsulation materials. [Background technology]
[0002] In order to protect semiconductors from humidity, gases, and impurities in the outside air, semiconductors have traditionally been encapsulated with semiconductor encapsulants containing resins and inorganic fillers. If the thermal expansion coefficient of the semiconductor encapsulant is much larger than that of the semiconductor, the semiconductor encapsulated by the semiconductor encapsulant may warp. For this reason, it is necessary to make the thermal expansion coefficient of the semiconductor encapsulant closer to that of the semiconductor. Since the thermal expansion coefficient of the resin is usually larger than that of the semiconductor, it is necessary to use an inorganic filler with a small thermal expansion coefficient. For this reason, silica, which has the lowest thermal expansion coefficient among industrial materials, has been used as the inorganic filler for semiconductor encapsulants.
[0003] In order to make the thermal expansion coefficient of the semiconductor encapsulant closer to that of the semiconductor, it is necessary to increase the silica filling rate in the semiconductor encapsulant. However, increasing the silica filling rate reduces the fluidity of the semiconductor encapsulant. For this reason, in order to prevent the fluidity of the semiconductor encapsulant from being reduced even when the semiconductor encapsulant contains silica at a high filling rate, spherical silica with high sphericity has been used as an inorganic filler in the semiconductor encapsulant. Furthermore, the production of micron-sized silica is more suitable for natural methods using natural silica as a raw material than for synthetic methods using metallic silicon or alkoxysilane as a raw material. However, spherical silica produced using natural silica contains a small amount of uranium. If spherical silica contains uranium, alpha rays will be emitted from the semiconductor encapsulant. These alpha rays are the cause of memory errors in semiconductors. For this reason, it is preferable that the uranium content in spherical silica is low. As an example of spherical silica with high sphericity and low uranium content, the low uranium spherical silica powder described in Patent Document 1 is known as a prior art. In the low uranium spherical silica powder described in Patent Document 1, when the spherical silica is produced, fine powder with a high uranium content is removed, thereby reducing the uranium content in the spherical silica to 0.9 ppb. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-60234 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in recent years, as semiconductor circuits have become more complex, there is a demand for further suppression of the emission of alpha rays from semiconductor encapsulants, which cause memory errors in semiconductors. For this reason, there is a demand for silicon dioxide powder with an even lower uranium content and higher sphericity. Therefore, an object of the present invention is to provide a silicon dioxide powder having a low uranium content and high sphericity. [Means for solving the problem]
[0006] As a result of extensive research, the present inventors have found that the above-mentioned problems can be solved by heating silicon dioxide in the presence of a halogen. The present invention is based on the above findings and has the following gist. [1] Silicon dioxide powder having a uranium content of 0.8 ppb by mass or less and a sphericity of 0.80 or more. [2] Specific surface area is 2.0m 2 / g or more. The silicon dioxide powder according to [1] above. [3] In the particle size distribution of the silicon dioxide powder, the particle diameter (d10) at which the cumulative frequency is 10% is 0.1 to 0.5 μm, the particle diameter (d50) at which the cumulative frequency is 50% is 0.3 to 12.0 μm, and the particle diameter (d90) at which the cumulative frequency is 90% is 1.5 to 22.0 μm. [1] or [2] above. Silicon dioxide powder. [4] The silicon dioxide powder according to any one of [1] to [3] above, having an iron content of 100 ppm by mass or less calculated as Fe2O3. [5] The silicon dioxide powder according to any one of the above [1] to [4], having an aluminum content of 500 ppm by mass or less calculated as Al2O3. [6] The silicon dioxide powder according to any one of [1] to [5] above, wherein the potassium content is 10 ppm by mass or less in terms of KO. [7] The silicon dioxide powder according to any one of the above [1] to [6], having a sodium content of 15 ppm by mass or less calculated as Na2O. [8] The silicon dioxide powder according to any one of the above [1] to [7], wherein the calcium content, calculated as CaO, is 15 ppm by mass or less. [9] The silicon dioxide powder according to any one of the above [1] to [8], having a magnesium content of 5 ppm by mass or less calculated as MgO.
[10] The silicon dioxide powder according to any one of the above [1] to [9], having a titanium content of 10 ppm by mass or less calculated as TiO2. Effect of the Invention
[0007] According to the present invention, it is possible to provide a silicon dioxide powder having a low uranium content and high sphericity. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a diagram showing an outline of the temperature and pressure conditions of the chlorine treatment in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The silicon dioxide powder of the present invention will be described below. The silicon dioxide powder of the present invention has a uranium content of 0.8 mass ppb or less and a sphericity of 0.80 or more.
[0010] (Uranium content) The uranium content of the silicon dioxide powder of the present invention is 0.8 mass ppb or less. If the uranium content of the silicon dioxide powder is greater than 0.8 mass ppb, when the silicon dioxide powder is used in a semiconductor encapsulant, the emission of alpha rays from the semiconductor encapsulant may be strong. From this viewpoint, the uranium content of the silicon dioxide powder is preferably 0.7 mass ppb or less, more preferably 0.6 mass ppb or less. The lower limit of the range of the uranium content of the silicon dioxide powder is not particularly limited, but is, for example, 0.1 mass ppb. The uranium content of the silicon dioxide powder can be measured by the method described in the Examples below.
[0011] (sphericity) The sphericity of the silicon dioxide powder of the present invention is 0.80 or more. If the sphericity of the silicon dioxide powder is less than 0.80, when the silicon dioxide powder is used in a semiconductor encapsulant, the flowability of the semiconductor encapsulant may be poor. From this viewpoint, the sphericity of the silicon dioxide powder is preferably 0.82 or more, more preferably 0.84 or more. The upper limit of the range of the sphericity of the silicon dioxide powder is usually 1.00. The sphericity of the silicon dioxide powder can be measured by the method described in the examples below.
[0012] (specific surface area) The specific surface area of the silicon dioxide powder of the present invention is preferably 2.0 m 2 / g or more. The specific surface area of the silicon dioxide powder is 2.0m 2 When the silicon dioxide powder is used in a semiconductor encapsulation material, the silicon dioxide powder can be more highly packed. From this viewpoint, the specific surface area of the silicon dioxide powder of the present invention is more preferably 4.0 m 2 / g or more. The specific surface area of the silicon dioxide powder of the present invention is preferably 20 m2 / g or less. The specific surface area of the silicon dioxide powder is 20m 2 When the specific surface area of the silicon dioxide powder is less than 1 / g, the silicon dioxide powder can be more easily mixed into the resin when used in a semiconductor encapsulant. The specific surface area of the silicon dioxide powder can be measured by the method described in the Examples below. The specific surface area may be adjusted to the above range by mixing fine powder and coarse powder.
[0013] (d10, d50 and d90) In the particle size distribution of the silicon dioxide powder of the present invention, the particle diameter (d10) at which the cumulative frequency is 10% is preferably 0.1 to 2.0 μm, the particle diameter (d50) at which the cumulative frequency is 50% is preferably 0.3 to 12.0 μm, and the particle diameter (d90) at which the cumulative frequency is 90% is preferably 1.5 to 22.0 μm. When the silicon dioxide powder has such a particle diameter, when the silicon dioxide powder is used in a semiconductor encapsulant, the silicon dioxide powder can be mixed more easily into the resin and the silicon dioxide powder can be contained at a higher filling rate. From this viewpoint, the particle size (d10) at which the cumulative frequency is 10% is more preferably 0.1 to 0.5 μm, the particle size (d50) at which the cumulative frequency is 50% is more preferably 0.3 to 5.0 μm, 0.3 to 4.0 μm, or 0.3 to 1.0 μm, and the particle size (d90) at which the cumulative frequency is 90% is more preferably 1.5 to 6.5 μm or 1.5 to 3.0 μm. The particle sizes can be measured by the method described in the Examples below.
[0014] (Average particle size) The average particle diameter of the silicon dioxide powder of the present invention is preferably 0.3 to 12.0 μm. When the average particle diameter of the silicon dioxide powder is 0.3 μm or more, the silicon dioxide powder can be more easily mixed into a resin when used in a semiconductor encapsulant. When the average particle diameter of the silicon dioxide powder is 12.0 μm or less, the silicon dioxide powder can be more highly loaded when used in a semiconductor encapsulant. From this viewpoint, the average particle diameter of the silicon dioxide powder of the present invention is more preferably 0.3 to 5.0 μm, 0.3 to 4.0 μm, or 0.3 to 1.0 μm. The average particle diameter of the silicon dioxide powder is the median diameter (particle diameter (d50) at which the cumulative frequency is 50%) of the particle size distribution measured by a laser diffraction scattering method.
[0015] The level of purity required by users for silicon dioxide powder is becoming higher and higher, and there is a problem that the impurity removal using magnets cannot meet the user's requirements for the purity of silicon dioxide powder. Impurities that are difficult to remove include uranium, titanium, iron, etc. In the present invention, impurities such as uranium, titanium, and iron can be removed from silicon dioxide powder to obtain high-purity silicon dioxide powder.
[0016] (Iron content) In the silicon dioxide powder of the present invention, the iron content is preferably 100 mass ppm or less, calculated as Fe2O3. When the iron content is 100 mass ppm or less, calculated as Fe2O3, when the silicon dioxide powder is used in a semiconductor encapsulant, it is possible to suppress the occurrence of short circuit defects between wirings of semiconductors, particularly semiconductors for automobiles. In addition, it is possible to suppress the decrease in whiteness of the silicon dioxide powder. From this viewpoint, the iron content is more preferably 80 mass ppm or less, and even more preferably 50 mass ppm or less, calculated as Fe2O3. The lower limit of the iron content is 0 mass ppm. The iron content can be measured by the measurement method described in the examples below.
[0017] (Aluminum content) In the silicon dioxide powder of the present invention, the aluminum content is preferably 550 mass ppm or less or 500 mass ppm or less, calculated as Al2O3. When the aluminum content is 550 mass ppm or less, calculated as Al2O3, the silicon dioxide powder can be used in a semiconductor encapsulant to suppress a decrease in the fluidity of the semiconductor encapsulant. From this viewpoint, the aluminum content is more preferably 400 mass ppm or less, and even more preferably 350 mass ppm or less, calculated as Al2O3. The lower limit of the aluminum content is 0 mass ppm. The aluminum content can be measured by the measurement method described in the examples below.
[0018] (Potassium content) In the silicon dioxide powder of the present invention, the potassium content is preferably 30 mass ppm or less, 20 mass ppm or less, or 10 mass ppm or less, calculated as K2O. When the potassium content is 30 mass ppm or less, calculated as K2O, the silicon dioxide powder can be used in a semiconductor encapsulant to suppress a decrease in moldability of the semiconductor encapsulant. In addition, the decrease in whiteness of the silicon dioxide powder can also be suppressed. The lower limit of the potassium content is 0 mass ppm. The potassium content can be measured by the measurement method described in the examples below.
[0019] (Sodium content) In the silicon dioxide powder of the present invention, the sodium content is preferably 15 mass ppm or less in terms of Na2O. When the sodium content is 15 mass ppm or less in terms of Na2O, when the silicon dioxide powder is used in a semiconductor encapsulant, the hardening of the semiconductor encapsulant can be suppressed from being delayed. In addition, the occurrence of wiring corrosion and the deterioration of the performance of the semiconductor element can be suppressed. The lower limit of the sodium content is 0 mass ppm. The sodium content can be measured by the measurement method described in the examples below.
[0020] (Calcium content) In the silicon dioxide powder of the present invention, the calcium content is preferably 20 ppm or less or 15 ppm by mass or less, calculated as CaO. When the calcium content is 15 ppm by mass or less, calculated as CaO, the silicon dioxide powder can be used in a semiconductor encapsulant to suppress a decrease in moldability of the semiconductor encapsulant. In addition, the decrease in whiteness of the silicon dioxide powder can also be suppressed. The lower limit of the calcium content is 0 ppm by mass. The calcium content can be measured by the measurement method described in the examples below.
[0021] (Magnesium content) In the silicon dioxide powder of the present invention, the magnesium content is preferably 10 mass ppm or less or 5 mass ppm or less in terms of MgO. When the magnesium content is 5 mass ppm or less in terms of MgO, the silicon dioxide powder can be used in a semiconductor encapsulant to suppress a decrease in moldability of the semiconductor encapsulant. In addition, the decrease in whiteness of the silicon dioxide powder can also be suppressed. The lower limit of the magnesium content is 0 mass ppm. The magnesium content can be measured by the measurement method described in the examples below.
[0022] (Titanium content) In the silicon dioxide powder of the present invention, the titanium content is preferably 10 mass ppm or less in terms of TiO2. When the titanium content is 10 mass ppm or less in terms of TiO2, it is possible to suppress the occurrence of short circuit defects between semiconductor wiring. The lower limit of the titanium content is 0 mass ppm. The titanium content can be measured by the measurement method described in the examples below.
[0023] (Number of magnetic particles in 50g of silicon dioxide powder) The level of purity required by users for silicon dioxide powder is becoming higher and higher, and there is a problem that the use of magnets to remove magnetizable foreign matter cannot meet the purity requirements of users for silicon dioxide powder. The number of magnetizable foreign matters having a particle size of 20 to 45 μm in 50 g of the silicon dioxide powder of the present invention is preferably 200 pieces / 50 g or less, 150 pieces / 50 g or less, 100 pieces / 50 g or less, 50 pieces / 50 g or less, 25 pieces / 50 g or less, or 10 pieces / 50 g or less. When the number of magnetizable foreign matters having a particle size of 20 to 45 μm in 50 g of the silicon dioxide powder is 600 pieces / 50 g or less, when the silicon dioxide powder is used in a semiconductor encapsulation material, it is possible to suppress the occurrence of short circuit defects between wiring of semiconductors, particularly semiconductors for automobiles. In addition, the decrease in the whiteness of the silicon dioxide powder can also be suppressed. The number of magnetizable foreign matters having a particle size of 20 to 45 μm in 50 g of the silicon dioxide powder can be measured by the method described in the Examples below. The number of magnetizable foreign matters having a particle diameter of 45 to 100 μm in 50 g of silicon dioxide powder is preferably 50 pieces / 50 g or less, 40 pieces / 50 g or less, 30 pieces / 50 g or less, 20 pieces / 50 g or less, 10 pieces / 50 g or less, 5 pieces / 50 g or less, or 2 pieces / 50 g or less. The number of magnetizable foreign matters having a particle diameter of 100 to 200 μm in 50 g of silicon dioxide powder is preferably 10 pieces / 50 g or less, 5 pieces / 50 g or less, 2 pieces / 50 g or less, 1 piece / 50 g or less, or 0 pieces / 50 g. The number of magnetizable foreign matters having a particle diameter of 200 to 275 μm in 50 g of silicon dioxide powder is preferably 1 piece / 50 g or less, or 0 pieces / 50 g.
[0024] (Ionic impurity content) In the silicon dioxide powder of the present invention, Fe 2+ The content of Fe is preferably 15 mass ppm or less. 2+ When the content of Fe is 15 mass ppm or less, when the silicon dioxide powder is used in a semiconductor encapsulation material, it is possible to suppress the occurrence of short circuit defects between wirings of semiconductors, particularly semiconductors for automobiles. In addition, it is possible to suppress the decrease in whiteness of the silicon dioxide powder. 2+ The lower limit of the Fe content is 0 ppm by mass. 2+ The content can be measured by the measurement method described in the Examples below. In addition, in the silicon dioxide powder of the present invention, Na + The content of Na is preferably 10 ppm by mass or less. +When the content of Na is 10 mass ppm or less, when the silicon dioxide powder is used in a semiconductor encapsulant, the delay in hardening of the semiconductor encapsulant can be suppressed. In addition, the occurrence of corrosion of wiring and the deterioration of the performance of semiconductor elements can be suppressed. + The lower limit of the content is 0 ppm by mass. + The content can be measured by the measurement method described in the Examples below. Furthermore, in the silicon dioxide powder of the present invention, Cl - The content of Cl is preferably 1.0 ppm by mass or less. - When the content of is 1.0 mass ppm or less, when the silicon dioxide powder is used in a semiconductor encapsulation material, it is possible to suppress the generation of HCl, which corrodes the lead wire. - The lower limit of the Cl content is 0 ppm by mass. - The content can be measured by the measurement method described in the Examples below.
[0025] (Method of manufacturing silicon dioxide powder) The silicon dioxide powder of the present invention can be produced, for example, by the following production method. The method for producing silicon dioxide powder includes the steps of: (A) preparing a silicon dioxide powder raw material; (B) melting and spheronizing the silicon dioxide powder raw material to produce unclassified molten spherical silicon dioxide powder; (C) classifying the unclassified molten spherical silicon dioxide powder to produce molten spherical silicon dioxide powders of different particle sizes; (D) blending the molten spherical silicon dioxide powders of different particle sizes to produce a blend of molten spherical silicon dioxide powders; (E) chlorinating the blend of molten spherical silicon dioxide powders; and (F) manufacturing the blend.
[0026] (Process (A)) In step (A), a silicon dioxide powder raw material is prepared. Examples of silicon dioxide powder raw materials include silica powder obtained by crushing natural silica, silica gel synthesized by a wet reaction between an alkali silicate and a mineral acid, crushed gel obtained from an alkoxysilane by a sol-gel method, and metal silicon particles. Among these silicon dioxide powder raw materials, crushed powder of natural silica is preferred because of the manufacturing cost and ease of adjusting the particle size of the raw material powder. In addition, in order to produce high-purity silicon dioxide powder using silica powder, silica powder of natural high-purity silica having a SiO2 purity of 99.5 mass% or more is usually used. However, since natural high-purity silica is rare, the raw material cost is high and the raw material supply may be unstable. In this method for producing silicon dioxide powder, high-purity silicon dioxide powder can be produced even using natural silica having a low SiO2 purity by chlorine treatment described later, so that the raw material cost can be reduced.
[0027] Silica powder, which is a raw material for silicon dioxide powder, is produced, for example, as follows: After washing the silica stone with water, it is pulverized using a pulverizer such as a vibration mill or a ball mill to produce silica powder. Then, the particle size distribution of the produced silica powder is adjusted using a vibration sieve or a classifier.
[0028] By adjusting the particle size of the silicon dioxide powder raw material, the specific surface area and particle size of the silicon dioxide powder of the present invention can be controlled. The particle size of the silicon dioxide powder raw material is generally, for example, 100 μm or less in average particle size, and may contain a large amount of fine powder of 1 μm or less, which is prone to agglomeration of powders.
[0029] (Process (B)) In step (B), the silicon dioxide powder raw material is melted and spheroidized to produce unclassified molten spherical silicon dioxide powder. For example, the silicon dioxide powder raw material is sprayed into a flame. As a result, the silicon dioxide powder raw material melts and is simultaneously spheroidized by surface tension. The droplets of the silicon dioxide powder raw material that have passed through the flame are quenched and become unclassified molten spherical silicon dioxide powder, which is amorphous spherical silicon dioxide. As the fuel gas for forming the flame, for example, propane, butane, propylene, acetylene, hydrogen, etc. are used, and as the supporting gas, for example, air, oxygen, etc. are used. The flame temperature is, for example, 2000 to 2400°C.
[0030] The sphericity of the unclassified molten spherical silicon dioxide powder can be adjusted, for example, by the heat of the flame and the injection amount of silicon dioxide powder raw material. If the heat of the flame is insufficient, the melting and spheroidization is insufficient, and the sphericity of the unclassified molten spherical silicon dioxide powder is low. If the heat of the flame is too high, the production cost of the unclassified molten spherical silicon dioxide powder increases. In addition, if the injection amount of the silicon dioxide powder raw material is too large, the particles are fused together after melting, and the sphericity of the unclassified molten spherical silicon dioxide powder decreases. If the injection amount of the silicon dioxide powder raw material is too small, the production cost of the unclassified molten spherical silicon dioxide powder increases.
[0031] (Process (C)) In step (C), the unclassified molten spherical silicon dioxide powder is classified to produce molten spherical silicon dioxide powder by particle size. For example, when collecting the unclassified molten spherical silicon dioxide powder obtained by passing the silicon dioxide powder raw material through a flame, it is classified according to particle size before collection. Coarse particles may be collected using a gravity settling chamber, a cyclone, etc., and fine particles may be collected using a bag filter, an electric dust collector, etc. The classified molten spherical silicon dioxide powder may then be further classified according to particle size using a classifier such as an air flow classifier, a vibrating sieve, or a cylindrical sieve.
[0032] (Process (D)) In step (D), molten spherical silicon dioxide powders of different particle sizes are blended to produce a blend of molten spherical silicon dioxide powders. For example, molten spherical silicon dioxide powders of different particle sizes are mixed in a ratio such that the molten spherical silicon dioxide powders of different particle sizes are combined to form the closest packing. The mixed molten spherical silicon dioxide powders are then mixed using a mixer such as a V-type blender, a double cone blender, or an air blender. This produces a blend of molten spherical silicon dioxide powders with good packing properties.
[0033] (Process (E)) In step (E), the blend of fused spherical silicon dioxide powder is chlorinated. The chlorine treatment of the blend of fused spherical silicon dioxide powder is described in detail below.
[0034] The chlorination treatment in step (E) includes a heating step in the presence of chlorine in which the blend is heated in the presence of chlorine. This causes impurities in the blend to be chlorinated into chlorides, which are then sublimated. As a result, the impurities are separated from the blend, and the purity of the blend is increased.
[0035] The heating temperature in the heating step in the presence of chlorine is not particularly limited as long as the impurities are chlorinated in the presence of chlorine to form chlorides and silicon dioxide is not chlorinated as much as possible. In addition, by adjusting the heating temperature in the heating step in the presence of chlorine to a temperature at which the desired impurities are chlorinated to form chlorides, the desired impurities can be removed from the blend. From the viewpoint of efficiently converting the impurities in the blend to chlorides and sublimating them in the presence of chlorine and from the viewpoint of suppressing the chlorination of silicon dioxide, the heating temperature in the heating step in the presence of chlorine is preferably 400 to 1200°C, more preferably 430 to 1100°C, and even more preferably 450 to 1050°C. In addition, from the viewpoint of converting the impurities in the blend to chlorides as much as possible and from the viewpoint of the efficiency of the chlorination treatment, the heating time in the heating step in the presence of chlorine is preferably 1 to 120 minutes, more preferably 1 to 60 minutes, and even more preferably 3 to 45 minutes. In addition, when the cycle described later is repeated, the above heating time is the heating time in the heating step in the presence of chlorine in each cycle. From the viewpoint of sublimating the chlorides generated by the chlorination of the impurities and from the viewpoint of the amount of chlorine in the atmosphere, the pressure around the blend in the heating step in the presence of chlorine is preferably 0.0001 to 100 kPa, more preferably 0.0005 to 50 kPa, and even more preferably 0.01 to 20 kPa. Since chlorine is corrosive, it is preferable to supply chlorine by mixing it with an inert gas such as nitrogen or argon. From the viewpoint of converting the impurities in the blend into chlorides, the content of chlorine in the atmosphere around the blend is preferably 30% by volume or more, more preferably 50% by volume or more, and even more preferably 80% by volume or more.
[0036] From the viewpoint that impurities in the center of silicon dioxide particles can be removed while maintaining the shape of silicon dioxide powder by heating in the presence of chlorine, the average particle size of silicon dioxide powder from which impurities are removed by heating in the presence of chlorine is preferably 0.002 to 100 μm, more preferably 0.005 to 50 μm, and even more preferably 0.01 to 20 μm. The average particle size of silicon dioxide powder is the median size of the particle size distribution measured by a laser diffraction scattering method.
[0037] The chlorine treatment may further include a first reduced pressure heating step in which the blend is heated under reduced pressure after the heating step in the presence of chlorine. This allows the chlorides generated by the chlorination of the impurities to be more completely sublimated. As a result, the purity of the blend can be further increased. In addition, the chlorine remaining in the blend can also be removed from the blend. If the chlorine content in the blend is high, HCl may be generated and corrode the lead wire when the blend is used as a semiconductor encapsulation material. From the viewpoint of more completely sublimating the chlorides generated by the chlorination of the impurities and from the viewpoint of the cost required for heating, the heating temperature in the first reduced pressure heating step is preferably 600 to 1250°C, more preferably 700 to 1200°C, and even more preferably 800 to 1150°C. From the viewpoint of more completely sublimating the chlorides generated by the chlorination of the impurities and from the viewpoint of the cost required for reducing the pressure, the pressure around the blend in the first reduced pressure heating step is preferably 0.0001 to 100 kPa, more preferably 0.0005 to 50 kPa, and even more preferably 0.01 to 20 kPa, in absolute pressure. From the viewpoint of more completely sublimating the chlorides generated by the chlorination of the impurities and from the viewpoint of productivity, the time for maintaining the reduced pressure in the first reduced pressure heating step is preferably 5 to 180 minutes, more preferably 10 to 120 minutes, and even more preferably 15 to 60 minutes. In addition, when the cycle described later is repeated, the time for maintaining the above-mentioned predetermined pressure is the time for maintaining the predetermined pressure in the first reduced pressure heating step of each cycle.
[0038] It is preferable to repeat the cycle consisting of the heating step in the presence of chlorine and the first heating step under reduced pressure two or more times. This allows more impurities to be separated from the blend, and the purity of the blend is further increased. From the viewpoint of increasing the purity of the blend and the viewpoint of productivity, it is preferable to repeat the cycle consisting of the heating step in the presence of halogen and the first heating step under reduced pressure 2 to 20 times, more preferably 3 to 15 times, and even more preferably 4 to 9 times.
[0039] The chlorine treatment preferably further includes a heating step in the presence of an inert gas in which the blend is heated in the presence of an inert gas. This makes it possible to more completely remove the chlorine remaining in the blend. As a result, the purity of the blend is further increased. Examples of the inert gas include nitrogen gas and argon gas. Of these inert gases, nitrogen gas is preferred from the viewpoint of cost.
[0040] The heating temperature in the heating step in the presence of an inert gas is preferably higher than the heating temperature in the heating step in the presence of chlorine, but is preferably 200° C. or less higher, more preferably 100° C. or less higher, and even more preferably 50° C. or less higher than the heating temperature in the heating step in the presence of a halogen.
[0041] The chlorine treatment may further include a second reduced pressure heating step in which the blend is heated under reduced pressure after the heating step in the presence of an inert gas. This allows the chlorine remaining in the blend to be more completely removed. As a result, the purity of the blend is further increased. From the viewpoint of removing chlorine from the blend and the cost required for heating, the heating temperature in the second reduced pressure heating step is preferably 600 to 1250°C, more preferably 700 to 1200°C, and even more preferably 800 to 1150°C. From the viewpoint of removing chlorine from the blend and the cost required for reducing pressure, the pressure around the blend in the second reduced pressure heating step is preferably 0.0001 to 100 kPa, more preferably 0.0005 to 50 kPa, and even more preferably 0.01 to 20 kPa, in absolute pressure. From the viewpoint of removing chlorine from the blend and from the viewpoint of productivity, the time for maintaining the reduced pressure in the second reduced pressure heating step is preferably 5 to 180 minutes, more preferably 10 to 120 minutes, and further preferably 15 to 60 minutes. When the cycle described below is repeated, the time for maintaining the above-mentioned predetermined pressure is the time for maintaining the predetermined pressure in the second reduced pressure heating step in each cycle.
[0042] It is preferable to repeat the cycle consisting of the heating step in the presence of an inert gas and the second heating step under reduced pressure two or more times. This makes it possible to more completely remove chlorine remaining in the blend product, and to further increase the purity of the blend product. From the viewpoint of increasing the purity of the blend product and the viewpoint of productivity, it is preferable to repeat the cycle consisting of the heating step in the presence of an inert gas and the second heating step under reduced pressure 2 to 20 times, more preferably 3 to 15 times, and even more preferably 5 to 12 times.
[0043] (Process (F)) In step (F), the blend is commercialized. Specifically, the blend may be subjected to a surface treatment using a silane coupling agent, or may be subjected to a classification treatment to precisely remove coarse particles, if desired. The blend that has undergone step (F) is shipped as a product.
[0044] (Semiconductor encapsulation material) The silicon dioxide powder of the present invention is preferably used for a semiconductor encapsulant. The semiconductor encapsulant is produced, for example, as follows using a resin composition containing the silicon dioxide powder of the present invention and a resin. First, the resin composition is kneaded while being heated with a roll or an extruder, and the kneaded product is stretched into a sheet and cooled. Then, the kneaded product is crushed or extruded into a line shape and cut while being cooled to obtain a semiconductor encapsulant as a crushed product. The crushed product may be a cylindrical tablet or a fine granular semiconductor encapsulant with a regular particle size and shape.
[0045] To seal a semiconductor using the above-mentioned semiconductor encapsulant, conventional molding methods such as transfer molding and compression molding are used. For example, to seal by transfer molding using a semiconductor encapsulant, a tablet-shaped semiconductor encapsulant is loaded into a pot equipped on a mold attached to a transfer molding machine, heated to melt, and then pressed with a plunger and further heated to harden and seal. In compression molding, particles of a resin composition are placed directly on a mold, and the molten molding material is slowly pressed onto a substrate to form the mold.
[0046] (Resin composition) The resin composition used for the semiconductor encapsulation material contains the silicon dioxide powder of the present invention and a resin as described above. The content of the silicon dioxide powder in the resin composition is preferably 10 to 95 mass%, more preferably 30 to 90 mass%.
[0047] Examples of resins that can be used include epoxy resin, silicone resin, phenol resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyamides such as polyimide, polyamideimide, and polyetherimide; polyesters such as polybutylene terephthalate and polyethylene terephthalate; polyphenylene sulfide, aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide-modified resin, ABS resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, and AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin.
[0048] Among these resins, epoxy resins having two or more epoxy groups in one molecule are preferred for preparing semiconductor encapsulants. Examples of epoxy resins include biphenyl type epoxy resins, phenol novolac type epoxy resins, orthocresol novolac type epoxy resins, epoxidized novolac resins of phenols and aldehydes, glycidyl ethers of bisphenol A, bisphenol F, bisphenol S, etc., glycidyl ester acid epoxy resins obtained by reacting polybasic acids such as phthalic acid and dimer acid with epochlorohydrin, linear aliphatic epoxy resins, alicyclic epoxy resins, heterocyclic epoxy resins, alkyl-modified polyfunctional epoxy resins, β-naphthol novolac type epoxy resins, 1,6-dihydroxynaphthalene type epoxy resins, 2,7-dihydroxynaphthalene type epoxy resins, bishydroxybiphenyl type epoxy resins, and epoxy resins into which halogens such as bromine have been introduced to impart flame retardancy. Among these, biphenyl type epoxy resins, orthocresol novolac type epoxy resins, bishydroxybiphenyl type epoxy resins, and epoxy resins with a naphthalene skeleton are preferred from the standpoint of moisture resistance and solder reflow resistance.
[0049] When the resin is an epoxy resin, the resin composition preferably contains a curing agent for the epoxy resin, or a curing agent for the epoxy resin and a curing accelerator for the epoxy resin. Examples of the curing agent for the epoxy resin include various phenolic resins; novolak type resins obtained by reacting one or a mixture of two or more selected from the group consisting of phenol, cresol, xylenol, resorcinol, chlorophenol, t-butylphenol, nonylphenol, isopropylphenol, octylphenol, and the like, with formaldehyde, paraformaldehyde, or paraxylene in the presence of an oxidation catalyst; polyparahydroxystyrene resin; bisphenol compounds such as bisphenol A and bisphenol S; trifunctional phenols such as pyrogallol and phloroglucinol; acid anhydrides such as maleic anhydride, phthalic anhydride, and pyromellitic anhydride; and aromatic amines such as metaphenylenediamine, diaminodiphenylmethane, and diaminodiphenylsulfone. In order to accelerate the reaction between the epoxy resin and the curing agent, the above-mentioned curing accelerators can be used, such as triphenylphosphine, benzyldimethylamine, and 2-methylimidazole.
[0050] The resin composition can be produced by blending the above-mentioned materials in predetermined amounts using a blender, a Henschel mixer, or the like, kneading the mixture using a heated roll, a kneader, a single-screw or twin-screw extruder, or the like, cooling the mixture, and pulverizing the mixture. EXAMPLES
[0051] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0052] The silicon dioxide powders of the examples and comparative examples were evaluated as follows. (Particle size) Using a laser scattering diffraction type particle size distribution analyzer (product name "CILAS920", manufactured by CILAS) or a particle size distribution analyzer (product name "LS230", manufactured by Beckman Coulter, Inc.), the particle size (d10) at which the cumulative frequency of the silicon dioxide powder is 10%, the particle size (d50) at which the cumulative frequency is 50%, and the particle size (d90) at which the cumulative frequency is 90% were measured. The particle size (d50) at which the cumulative frequency is 50% is the average particle size.
[0053] (specific surface area) The specific surface area of the silicon dioxide powder was measured by the BET method using a specific surface area measuring device (product name "Macsorb HM model-1208", manufactured by MACSORB).
[0054] (sphericity) Measurements were performed using a wet flow type particle size and shape analyzer (product name "FPIA-3000", manufactured by Malvern Panalytical). After dispersing the sample in pure water, the liquid was poured into a planar extensional flow cell, and 100 or more amorphous silica powder particles moving in the cell were recorded as images using an objective lens. The average circularity was calculated from the recorded images and the following formula (1). In formula (1), HD represents the circular equivalent diameter, which is calculated from the ratio of the projected area of the target particle to the area of a perfect circle. PM represents the projected perimeter of the target particle. The average value of 200 silicon dioxide particles calculated in this way was taken as the average circularity. Equation (1): Average circularity = π HD / PM From this average circularity, the formula: average sphericity = (average circularity) 2 The average sphericity was calculated by
[0055] (U (uranium) content) A sample solution was prepared by thermal decomposition of silicon dioxide powder using hydrofluoric acid and nitric acid. The sample solution was then quantitatively analyzed using an inductively coupled plasma mass spectrometer (Hitachi Instruments, Ltd., measurement limit: 0.01 ppb) to measure the U (uranium) content.
[0056] (Number of magnetic particles in 50g of silicon dioxide powder) 50 g of silicon dioxide powder and 800 g of ion-exchanged water were added to a 1000 mL beaker to prepare a slurry. The slurry was inverted at a rotation speed of 550 rpm and at 5-second intervals using a stirrer, and a bar magnet with a length of 150 mm, a diameter of 25 mm, and a magnetic force of 12000 gauss covered with a 20-μm-thick rubber cover was immersed therein for 1 minute to capture the magnetizable particles. The bar magnet that had captured the magnetizable particles was taken out of the slurry, the rubber cover was removed over an empty beaker, and the magnetizable particles were detached while washing the rubber cover with ion-exchanged water, and the magnetizable particles were dispersed in water. The obtained dispersion was filtered through a suction filtration device equipped with a 25-mm-diameter nylon filter (opening 13 μm) to recover the magnetizable particles on the nylon filter. The nylon filter on which the magnetizable particles were recovered was set on a microscope, and while moving the entire filter area at a magnification of 100 times, the number of magnetizable particles of 20 μm or more among the magnetizable particles recovered on the nylon filter was counted.
[0057] (Content of ionic impurities) ><Method for measuring Fe ions> 30 mL of aqua regia adjusted so that the volume ratio of concentrated nitric acid, concentrated hydrochloric acid, and water was 1:5:34 and 5 g of a sample of silicon dioxide powder were placed in a 100 mL beaker and heat-treated. After cooling, centrifugation was performed, and the obtained supernatant was used as a measurement solution. This measurement solution was measured with an air-acetylene atomic absorption photometer, and the absorbance at 248.3 nm was measured. ><Method for measuring Na ions> 10 g of a sample of silicon dioxide powder and 70 mL of ion-exchanged water were placed in a PE container and shaken for 1 minute. Then, it was placed in a dryer, left at 95 °C for 20 hours, and then cooled. Water corresponding to the evaporated amount was added for quantification. Then, centrifugation was performed, and the supernatant was recovered and used as a measurement solution. This measurement solution was measured with an air-acetylene atomic absorption photometer, and the absorbance at 589.0 nm was measured. ><Method for measuring chloride ions> 10 g of silicon dioxide powder sample and 70 mL of ion-exchanged water were placed in a PE container and shaken for 1 minute. The container was then placed in a dryer and left at 95°C for 20 hours, after which it was cooled. The amount of water that had evaporated was added to obtain a quantitative amount. The sample was then centrifuged, and the supernatant was collected and used as the measurement solution. This measurement solution was then measured using an ion chromatograph. For the Fe ions, Na ions, and chlorine ions, standard stock solutions (1,000 ppm) were prepared and then diluted to prepare standard solutions. Calibration curves were created from the relationship between the absorbance and the concentration of each ion.
[0058] (Aluminum, iron, potassium, sodium, calcium, magnesium and titanium content) A sample solution was prepared by thermal decomposition of silicon dioxide powder using hydrofluoric acid and nitric acid. The sample solution was then quantitatively analyzed using an inductively coupled plasma mass spectrometer to measure the aluminum content converted to Al2O3, the iron content converted to Fe2O3, the potassium content converted to K2O, the sodium content converted to Na2O, the calcium content converted to CaO, the magnesium content converted to MgO, and the titanium content converted to TiO2 in the silicon dioxide powder.
[0059] Silicon dioxide powder was subjected to the following chlorine treatment to produce silicon dioxide powders A to G. A chlorine atmosphere batch furnace (product name "Model 480", manufactured by Noritake Co., Ltd.) was used for the chlorination. The temperature and pressure conditions for the chlorination are outlined in Figure 1. The operating conditions for the chlorination are as follows:
[0060] (Chlorination operating conditions) (Gas used) Purity of chlorine gas supplied to chlorine atmosphere batch furnace: 100% Purity of nitrogen gas supplied to chlorine atmosphere batch furnace: 99.998% (Heating process in the presence of chlorine) Flow rate of chlorine gas supplied to the chlorine atmosphere batch furnace: 5L / min Flow rate of nitrogen gas supplied to the chlorine atmosphere batch furnace: 20 L / min Chlorine gas content in the total gas supplied to the chlorine atmosphere batch furnace: 20% by volume Heating temperature: 900℃ Heating time in the heating step in the presence of chlorine in one cycle: 5 minutes Pressure: 91.3kPa Note: First, the inside of the batch furnace was depressurized to 0.01 kPa before chlorine gas and nitrogen gas were supplied. Also, the heating rate from room temperature to 900°C was 5°C / min. (First reduced pressure heating step) Heating temperature: 900℃ Pressure: 0.13kPa Time to maintain the above pressure in the first reduced pressure heating step in one cycle: 2 minutes (Cycle consisting of a heating step in the presence of chlorine and a first heating step under reduced pressure) Number of cycles: 6
[0061] (Heating process in the presence of inert gas) Flow rate of nitrogen gas supplied to the chlorine atmosphere batch furnace: 20 L / min Heating temperature: 1000℃ Heating time in the heating step in the presence of inert gas in one cycle: 5 minutes Pressure: 91kPa Note: When moving from the first depressurization step to the heating step in the presence of an inert gas, the pressure inside the batch furnace was reduced to 0.01 kPa to remove the chlorine gas inside the batch furnace, and then nitrogen gas was supplied. (Second reduced pressure heating step) Heating temperature: 1000℃ Pressure: 0.13kPa Time to maintain the above pressure in the second reduced pressure heating step in one cycle: 2 minutes (Cycle consisting of a heating step in the presence of an inert gas and a second heating step under reduced pressure) Number of cycles: 4 Note: After completing the 4 cycles, the pressure inside the batch furnace was reduced to 0.01 kPa and then returned to atmospheric pressure. Silicon dioxide powder B to silicon dioxide powder G were produced in the same manner as silicon dioxide powder A, except that the silicon dioxide powders shown in Table 1 were used.
[0062] The results are shown in Table 1. [Table 1]
[0063] As shown by the above examples, it was possible to produce silicon dioxide powder having a uranium content of 0.8 mass ppb or less and a sphericity of 0.80 or more.
Claims
1. The uranium content is 0.8 ppb by mass or less, The sphericity is 0.80 or more, In the particle size distribution, the particle diameter (d10) at which the cumulative frequency is 10% is 0.1 to 0.5 μm, the particle diameter (d50) at which the cumulative frequency is 50% is 0.3 to 12.0 μm, and the particle diameter (d90) at which the cumulative frequency is 90% is 1.5 to 22.0 μm.
2. Specific surface area is 2.0m 2 The fused spherical silicon dioxide powder according to claim 1, wherein the molecular weight is 1 / g or more.
3. The iron content is Fe 2 O 3 The molten spherical silicon dioxide powder according to claim 1 or 2, wherein the content is 100 ppm by mass or less in terms of the total mass of the silicon dioxide powder.
4. The aluminum content is Al 2 O 3 The molten spherical silicon dioxide powder according to any one of claims 1 to 3, wherein the total amount of the molten spherical silicon dioxide powder is 500 ppm by mass or less in terms of the total amount of the silicon dioxide.
5. The potassium content is K 2 The molten spherical silicon dioxide powder according to any one of claims 1 to 4, wherein the O content is 10 ppm by mass or less.
6. The sodium content is Na 2 The molten spherical silicon dioxide powder according to any one of claims 1 to 5, wherein the O content is 15 ppm by mass or less.
7. The molten spherical silicon dioxide powder according to any one of claims 1 to 6, wherein the calcium content, calculated as CaO, is 15 ppm by mass or less.
8. The molten spherical silicon dioxide powder according to any one of claims 1 to 7, wherein the magnesium content, calculated as MgO, is 5 ppm by mass or less.
9. The titanium content is TiO 2 The molten spherical silicon dioxide powder according to any one of claims 1 to 8, wherein the total amount of the molten spherical silicon dioxide powder is 10 ppm by mass or less in terms of mass.
Citation Information
Patent Citations
High purity spherical silica and production thereof
JP1995069617A
Production of spherical silica powder with low uranium content, and silica powder
JP1999060234A
Crystalline silica particle material and method for manufacturing same, slurry composition containing crystalline silica particle material, and resin composition containing crystalline silica particle material
WO2017188301A1
Sol-gel silica powder and method for producing same
WO2018096876A1